Absent masculinity and feminine resilience : a post colonial analysis of media discourses of female-headed households in South Africa - Letsoalo, Koketso Sophia (My University, 2022)
South Africa experiences a high rate of absent fathers and this makes single-mother households a prominent family structure in the country. There are many framings and discourses of single mother households in the media, ranging from the critical to the negative and occasional positive ones. But in these discourses, do the resilience, strength, and hard work of single mothers form part of the framing of single mothers in South Africa? The destruction of the Black family structure is one of the disastrous legacies of colonialism and apartheid in South Africa. The discoveries of gold and diamonds brought a rapid social and economic transformation in the country, and Black families bore the brunt of this transformation which changed the Black family structure to date. The implementation of colonial and apartheid policies such as the migrant labour system was set to grow the White economy and achieve this goal by getting cheap labour from Black males in the homelands. The migrant labour system forced Black men to work in the mines leaving their families behind as the men were placed in single-sex hostels. This system, therefore, resulted in many households being fatherless and women or mothers wielding the household responsibilities while their husbands were in the cities. This historical context is important in studying current absent fatherhood and single mother households in South Africa. The study used a historical approach to understand the Black family structure prior colonial era, and how it transitioned during colonialism, and apartheid up and in the current post-apartheid era. This study is built on the theories of post-coloniality, the intersectional burden of femininity, media framing, and it engages critical theoretical scholars such as Homi Bhabha, Arlie Hochschild, Simone de Beauvoir, Bell hooks, and Kimberle Crenshaw amongst others. Through these theoretical lenses, I examined the influence of colonialism and apartheid on the contemporary father absence and female-headed households. The theoretical lenses were further used to examine how the past influence the future and how women's issues are addressed. I also examined the role of media in the (re)presentation of female-headed households. The study tackled three objectives: to examine the media discourse of single motherhood in South Africa; to analyze if women’s resilience in matrifocal families forms part of the media discourse of single motherhood, and lastly to explore the effects of colonialism and apartheid on Black family structure and their consequences in South Africa today. Data were collected through an analysis of a documentary film titled “Last Grave at Dimbaza”. This was an apartheid-era documentary that captured the lives of both Black and White families during apartheid. I examined this film to locate data that capture the media discourse about absent fatherhood during apartheid–which directly reflects the South African colonial-apartheid influence on this phenomenon. Data were also collected from online newspaper publications such as IOL, TimesLive, and News24 on stories about single-motherhood within a period of three years from January 2018 to December 2020 to address the media construction of single-motherhood in the post-apartheid era. The results of the study show that media discourse tends to perpetuate a normative negative and global trend of stereotyping mothers who receive social grants. Single mothers are portrayed as a group that misappropriates state resources, who pocket state money to meet their personal needs. They are thus stereotyped as social burdens on the state finances and contribute to the country's economic risks. Women are portrayed as victims of apartheid without any agency in the absence of their men. The study revealed that women had to find ways to survive or feed their families while waiting for their husbands to send money. However, what is missing in this portrayal is how women in the Bantustans survived under the migrant labour and apartheid laws and policies. Thus, this study found that coloniality seems to continue to shape the Black family structure and that the father's absence in the black society persists and this pattern is transmitted from one generation to another. It was also revealed in this study that when the father is absent, he leaves a trait of absence that his son becomes likely to inherit. Black families are still built from the bourgeois colonialist environment, absent fatherhood and female-headed households are the legacies of colonialism as it is inherited from the colonial background and compounded by socio-economic challenges. Single mothers who are confronted with multiple burdens in raising their children should have their agency, resilience, and challenging work acknowledged. They should be celebrated, not scorned.
Thesis (M. A. (Communication Studies)) -- University of Limpopo, 2022
Keywords: Masculinity; Postcolonialism; Apartheid; Single mothers; Absentee fathers; Post-apartheid era--South Africa; Masculinity; Postcolonialism; Apartheid; Single mothers; Absentee fathers; Post-apartheid era -- South Africa